Profile of micronucleus frequencies and DNA damage in different species of fish in a eutrophic tropical lake - Grisolia, Cesar Koppe (2009)
Lake Paranoá is a tropical reservoir for the City of Brasilia, which became eutrophic due to inadequate sewage treatment associated with intensive population growth. At present, two wastewater treatment plants are capable of processing up to 95% of the domestic sewage, thereby successfully reducing eutrophization. We evaluated both genotoxic and cytotoxic parameters in several fish species (Geophagus brasiliensis, Cichla temensis, Hoplias malabaricus, Astyanax bimaculatus lacustres, Oreochromis niloticus, Cyprinus carpio and Steindachnerina insculpita) by using the micronucleus (MN) test, the comet assay and nuclear abnormality assessment in peripheral erythrocytes. The highest frequencies of MN were found in Cichla temensis and Hoplias malabaricus, which were statistically significant when compared to the other species. However, Steindachnerina insculpita (a detritivorous and lake-floor feeder species) showed the highest index of DNA damage in the comet assay, followed by C. temensis (piscivorous). Nuclear abnormalities, such as binucleated, blebbed, lobed and notched cells, were used as evidence of cytotoxicity. Oreochromis niloticus followed by Hoplias malaricus, ominivorous/detritivotous and piscivorous species, respectively, presented the highest frequency of nuclear abnormalities, especially notched cells, while the herbivorous Astyanax bimaculatus lacustres showed the lowest frequency compared to the other species studied. Thus, for biomonitoring aquatic genotoxins under field conditions, the food web should also be considered.